1968
DOI: 10.1104/pp.43.7.1146
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis in Relation to Ripening of Pome Fruits

Abstract: Abstract. Protein synthesis by intact Bartlett pear fruits was studied with ripening as measured by flesh softening, chlorophyll degradation, respiration, ethylene synthesis, and malic enzyme activity. Protein synthesis is required for normal ripening, and the proteins synthesized early in the ripening process are, in fact, enzymes required for ripening. l"C-Phenylalanine is differentially incorporated into fruit proteins separated by acrylamide gel electrophoresis of pome fruits taken at successive ripening s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
65
0
3

Year Published

1971
1971
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(77 citation statements)
references
References 18 publications
(5 reference statements)
9
65
0
3
Order By: Relevance
“…An increase in polysome prevalence early in the climacteric is consistent with previous results demonstrating an increase in protein synthesis during this period in avocado (f 7), banana (4), pear (8), and other fruits (23). Moreover, the finding that the greatest part of the increase in polysome prevalence in early climacteric avocado is due to a generic increase in constitutive mRNAs on polysomes, is corroborated by Brady and O'ConneHl's (4) results for banana which showed no significant differences between the proteins synthesized in preclimacteric banana fruit and during the peak of protein synthesis early in the climacteric.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…An increase in polysome prevalence early in the climacteric is consistent with previous results demonstrating an increase in protein synthesis during this period in avocado (f 7), banana (4), pear (8), and other fruits (23). Moreover, the finding that the greatest part of the increase in polysome prevalence in early climacteric avocado is due to a generic increase in constitutive mRNAs on polysomes, is corroborated by Brady and O'ConneHl's (4) results for banana which showed no significant differences between the proteins synthesized in preclimacteric banana fruit and during the peak of protein synthesis early in the climacteric.…”
supporting
confidence: 80%
“…McGlasson et al (12) and Frenkel et al (8) found that they could inhibit ripening of thick banana slices and Bartlett pear fruit, respectively, with cycloheximide but not the respiratory climacteric. Quazi and Freebairn (16) found that bananas ripened normally under diminished 02 tension, while having a much reduced respiratory climacteric.…”
mentioning
confidence: 99%
“…Three days after the ethylene was administered, i.e. day 9 (Fig. 6), no difference in production rate between the ethylene-treated and untreated fruits was discerned.…”
Section: Resultsmentioning
confidence: 94%
“…The method used was essentially that of Frenkel et al (9) with modifications to improve distribution and to ensure sterility. The fruit were surface-sterilized in diluted household bleach (final sodium hypochlorite concentration 1.3%, w/v) for 15 min then rinsed thoroughly.…”
Section: Methodsmentioning
confidence: 99%
“…It is clear that fruit ripening is a complex of several processes which may be unrelated to one another once they have been initiated by ethylene in its role as the fruit ripening hormone (11,12,15). Although it has been thought that the respiratory increase in ripening fruits might be regarded as the summation of the energy requirements of other events in the ripening complex, recent work (5,6,18) (4. 14).…”
Section: Effect Of Ethylene Treatment On the Respiration Of Potatomentioning
confidence: 99%